Floods : people at risk, strategies for prevention - Miller, John B. (UN New YorkUS, 1997)
Discusses basic hydrological ideas; flood plain management; structural and non-structural measures. Look at how the dams built for water supply can be designed safely against floods. Focuses on emergency response and emphasizes the key points to be considered in flood alleviation and protection.